Phenotypic Characterization According to The Feather Color of Indigenous Muscovy Ducks Bred in The Back Yard in Brazzaville, The Congo - Bati, J.B.; Biza-Koukaba, C.K.; Banga-Mboko, H; Mfoukou-Ntsakala, A.; Bakoutana, D.; Adzona, P.P.; Hornick, J.L.; Leroy, P.L. (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract.Â In Congo, waterfowl genetic resources are constituted by native population of Muscovy ducks that play an important role in food security. The present study aimed to identify and to characterize strains bred in the back yard in the households in Brazzaville. A sample of 154 households drawn over seven districts of Brazzaville was enrolled in the survey. Adults ducks found in the households were identified, pictured by a key of determination and then compared by using the multi resolution analysis image method. The survey recorded 13 strains in which four were considered as newly since they have never been reported elsewhere. These strains received temporally the name of the districts where they have been identified for the first time MakelÃ©kÃ©lÃ© 1 (0.34%, n=6), MakÃ©lÃ©kÃ©lÃ© 2 (0.11%, n =2), Poto poto 1 Â (0.28%, n=5) and in Poto poto 2 (0.11%, n=2). Finally, the survey reported nine classical Â strains such as Â black plumage, duclair, white, tortora, sepia, chocolate, lavender, grey and canizie. The apparent wide variation in plumage colors is an indication that the duck populations have not been âpurifiedâ through selective breeding. In the context of the valorization of poultry biodiversity, this work represents a step toward a better knowledge of the production abilities of local ducks breeds in Congo.Â Key words: Muscovy ducks, color feather, strains, Congo.Â Abstrak.Â Sumber daya genetik unggas air di Kongo mencakup populasi itik lokal yang memegang peranan penting dalam ketahanan pangan. Penelitian ini bertujuan mengidentifikasi dan menggolongkan jenis itik yang dipelihara di pekarangan rumah di Brazzaville. Sampel penelitian menggunakan 154 responden rumah tangga yang tersebar di 7 wilayah Brazzaville. Itik dewasa diidentifikasi dari pekarangan, dan dibandingkan dengan metode Analisis Multi Resolusi. Survey mencatat 13 jenis peranakan, 4 diantaranya dianggap baru karena belum pernah dilaporkan di studi manapun. Jenis ini sementara dinamai sesuai distrik tempatnya pertama ditemukan, yaitu MakelÃ©kÃ©lÃ© 1 (0,34%, n=6), MakÃ©lÃ©kÃ©lÃ© 2 (0,11%, n =2), Poto poto 1Â (0,28%, n=5) dan di Poto poto 2 (0,11%, n=2). Berdasarkan survei didapatkan sembilan jenis klasik yaitu bulu hitam, duclair, putih, tortora, sepia, coklat, lavender, abu-abu dan canizie. Banyaknya ragam warna bulu adalah indikasi bahwa populasi itik belum âdimurnikanâ melalui seleksi. Dalam konteks penetapan nilai keanekaragaman hayati unggas, penelitian ini mewakili sebuah langkah menuju pengetahuan yang mendalam akan kemampuan produksi itik yang berkembang di Kongo.Â Kata kunci: itik Muscovy, warna bulu, strain, Kongo